A novel HPLC column switching method coupled to ICP-MS/QTOF for the first determination of selenoprotein P (SELENOP) in human breast milk. (15th August 2020) - Arias-Borrego, A.; Callejón-Leblic, B.; Rodríguez-Moro, G.; Velasco, I.; Gómez-Ariza, J.L.; García-Barrera, T.
Graphical abstract: Highlights: The presence of selenoprotein P in human breast milk has been demonstrated by MS. Selenium concentration in colostrum follows the order: GPX ≈ SELENOP > SeCA > SeMB. A mean concentration of 20.1 ± 1.0 ng Se g −1 is present as SELENOP (31% of total Se). Quantification/identification of selenospecies was performed by SUID-ICP-MS and MS. Abstract: In this work, we describe for the first time the presence of selenoprotein P in human breast milk. To this end, a novel analytical method has been developed based on a two-dimensional column switching system, which consisted of three size exclusion columns and one affinity column coupled to inductively coupled plasma mass spectrometry (ICP-MS). The method combines the accurate quantification of selenoproteins and selenometabolites by species unspecific isotopic dilution ICP-MS, with unequivocal identification by quadrupole-time-of-flight mass spectrometry. Several selenopeptides, which contain the amino acid selenocysteine (U, SeCys), were identified after tryptic digestion followed by their separation. The results reveal that the relative selenium concentration in colostrum follows the order: glutathione peroxidase (GPX) ≈ selenoprotein P (SELENOP) > selenocystamine (SeCA) > other selenometabolites (SeMB), in contrast with previously published papers (GPX > SeCA > selenocystine > selenomethionine). A mean concentration of 20.1 ± 1.0 ng Se g −1 as SELENOP (1.45 μg SELENOP/g) was determined in colostrum (31% of total selenium).